Characterization and application of silver nanoparticles decorated electrospun nanofiber loaded with naringenin - AYAZ SEYHAN, SERAP; BİLĞİÇ ALKAYA, DİLEK; CESUR, SÜMEYYE; GÜNDÜZ, OĞUZHAN (My University, 2022)
Nanoparticles are an innovative class of functional materials. Silver nanoparticles (AgNPs) are extensively applied in different fields of science, such as biomedical science, including antibacterial, antiviral, anti-inflammatory, and anticancer therapies. Also, AgNPs are being used to produce various biomedical products to prevent infection. The application of AgNPs has been widened due to recent advances in nanotechnology. AgNPs have several important implications including medical diagnostics, therapeutics, antioxidant, antibacterial, and cytotoxic properties. Many natural biomolecules in plants (inactivated plant tissue, plant extracts and living plant) such as proteins/enzymes, amino acids, polysaccharides, alkaloids, alcoholic compounds, and vitamins could be involved in bioreduction, formation and stabilization of AgNPs. Naringenin (4′,5,7-trihydroxyflavanone) (NRG) is a bioflavonoid widely present in fruits; it has been reported to have antioxidant, free radical scavenging, anticancer, anti-inflammatory, immunomodulating and memory enhancing properties. Its antioxidant effects may make NRG a potential drug for treating Alzheimer disease (AD). Recently, NRG was found to exhibit neuroprotective effect in models of Parkinson's disease (PD) and AD, such as the ICV-STZ-induced mode of AD and the 6-OHDA model of PD. Nanocomposite materials consisting of metallic nanoparticles incorporated in or with polymers have attracted much attention because of their distinct optical, electrical and catalytic properties, which have potential applications in the fields of catalysis, bioengineering, photonics, and electronics. Silver nanoparticles have been immobilized into polymer-based nanofibers to introduce hybrid multifunctional substrates for a variety of applications. In this study, nanostructured metal-polymer hybrid (AgNPsNRG-PLA) nanofibers were obtained by electrospinning technique.The nanostructured metal-polymer hybrid (AgNPs-NRG-PLA) nanofibers were characterized by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), thermal analysis (DSC) and tensile strength and physical analyzes such as density, surface tension, particle viscosity were performed.
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG)